Modelling and simulation in sport and exercise - Baca, Arnold; Perl, Jurgen (Routledge research in sport and exercise science, 2019)
Modelling and simulation techniques are of central importance to conducting research in sport and exercise science, informing data collection and helping to analyze patterns of movement and physical performance. This is an important reference for any active researcher or upper-level student in sport and exercise science with an interest in mathematical modelling, computer science or simulation techniques.